THE 20TH CENTURY ISLAMIC EDUCATION IN MANDAILING LAND: A Study of the Intellectual Legacy of Sheikh Ali Hasan Ahmad Ad-Dary (1915-1998) - Waldi, Irfa; Daulay, Haidar Putra; Asari, Hasan (UIN Sumatera Utara, 2023)
Abstract: This article examines Sheikh Ali Hasan Ahmad Addary's role in Islamic education. The main methodology used in this study is historical analysis using a character study approach. A strong scientific spirit and religious family influences were important contributors to Addary's activity. Addary concentrated on three things throughout his life, including bureaucracy, social religion and islamic education initiator. He was an ASN (civil servant) of the Ministry of Religion and the founding Dean of IAIN Imam Bonjol Padang's Faculty of Education Padangsidimpuan branch. Addary was involved in NU's social and religious life, and he was a well-known intellectual figure in the area of Islamic education.Keywords: Islamic Education, Mandailing Ulama, Ali Hasan Ahmad Addary